Myeloproliferative neoplasms (MPNs) have a significant impact on patients' overall health and productivity: the MPN Landmark survey. Issue 1 (December 2016) - Mesa, Ruben; Miller, Carole; Thyne, Maureen; Mangan, James; Goldberger, Sara; Fazal, Salman; Ma, Xiaomei; Wilson, Wendy; Paranagama, Dilan; Dubinski, David; Boyle, John; Mascarenhas, John
Abstract Background The Philadelphia chromosome−negative myeloproliferative neoplasms (MPN) myelofibrosis (MF), polycythemia vera (PV), and essential thrombocythemia (ET) negatively affect patient quality of life (QoL) and are associated with increased risk of mortality. Methods The MPN Landmark survey was conducted from May to July 2014 in patients with MF, PV, or ET under active management in the United States. The survey assessed respondent perceptions of disease burden and treatment management and included questions on overall disease burden, QoL, activities of daily living, and work productivity. Outcomes were further analyzed by calculated (ie, not respondent-reported) prognostic risk score and symptom severity quartile. Results The survey was completed by 813 respondents (MF, n = 207; PV, n = 380; ET, n = 226). The median respondent age in each of the 3 MPN subtypes ranged from 62 to 66 years; median disease duration was 4 to 7 years. Many respondents reported that they had experienced MPN-related symptoms ≥1 year before diagnosis (MF, 49 %; PV, 61 %; ET, 58 %). Respondents also reported that MPN-related symptoms reduced their QoL, including respondents with low prognostic risk scores (MF, 67 %; PV, 62 %; ET, 57 %) and low symptom severity (MF, 51 %; PV, 33 %; ET, 15 %). Many respondents, including those with a low prognostic risk score, reported that their MPN had caused them to cancel planned activities or call in sick to work at least once in the preceding 30 days (cancel planned activities: MF, 56 %; PV, 35 %; ET, 35 %; call in sick: MF, 40 %; PV, 21 %; ET, 23 %). Conclusions These findings of the MPN Landmark survey support previous research about the symptom burden experienced by patients with MPNs and are the first to detail the challenges that patients with MPNs experience related to reductions in activities of daily living and work productivity.